Why and how power disparity harm team performance - Luo, Shiwen; Furuoka, Fumitaka; Zuo, Xuelian (Frontiers in Psychology, 2025)
IntroductionPower disparity, defined as the unequal control over valuable resources within teams, has been shown to negatively impact overall team performance, though the mediating mechanisms and boundary conditions of this relationship remain inadequately explored. Grounded in power conflict theory, this study develops a conceptual model that incorporates team conflict—comprising both relationship conflict and task conflict—as a mediator, and power congruence as a moderator, to systematically explain why and how power disparity influences team performance.MethodsSurvey data were collected from 62 teams. The proposed hypotheses concerning the mediating and moderating effects were tested through a series of statistical analyses, including reliability and validity tests, confirmatory factor analysis, and hierarchical regression.ResultsPower disparity was found to negatively affect team performance through increased relationship conflict, while also positively influencing team performance via task conflict. However, the negative indirect effect through relationship conflict was significantly stronger than the positive effect through task conflict. Furthermore, power congruence moderated these mediating pathways: it attenuated the negative effect of relationship conflict and strengthened the positive effect of task conflict. These findings reveal a dual pathway through which power disparity affects team performance, with the overall effect being negative due to the stronger detrimental role of relationship conflict. The moderating role of power congruence helps mitigate harmful conflict and promotes beneficial debate, offering theoretical contributions to power conflict theory and practical implications for designing more effective team power structures.